Structure and Social Function of the Folk Song Lullaby Ngasoh Anuak Masyarakat in the Village of Sumur Anyir - Kurniawan, Doni; Tory Prasetya, Muhammad; Nurizzati, (Jurnal Indonesia Sosial Sains, 2026)
The folk song Tale Ngasoh Anuak is part of the oral tradition used as a lullaby in the Kerinci ethnic community, particularly in Dusun Empih, Sumur Anyir Village, Sungai Penuh City, Jambi Province. This song has been passed down orally through generations as part of the traditional child-rearing system. Beyond its aesthetic value, it holds significant social functions in the lives of the Kerinci people. This study aims to describe the physical structure of the Tale Ngasoh Anuak folk song and uncover its social functions within the Kerinci community, especially in the context of child-rearing and cultural identity preservation. This research employed a qualitative method with a descriptive approach. Data were collected through observation, interviews, and documentation to analyze the song's physical structure and social functions. The study found that Tale Ngasoh Anuak possesses characteristics of traditional poetry, consisting of lines, stanzas, diction, sound, themes, tone, and messages. The sound elements include rhyme, alliteration, assonance, euphony, cacophony, and sound repetition, which create a soothing atmosphere. Thematically, the song reflects parental affection, socio-economic realities, hopes for children's future, and the development of character and social ethics. In addition to its aesthetic value, the song serves as entertainment, family communication, character education, and a medium for transmitting oral traditions that strengthen the cultural identity of the Kerinci community.